Ayurvedic Management of Ovulatory Dysfunction in PCOS - Giby Thomas; Anjali TS; Archana Asok (International Journal of Ayurveda and Pharma Research, 2025)
Polycystic ovarian syndrome, is a common endocrine disorder in women of reproductive age that can lead to anovulation. This disorder accounts for 30% of all infertility cases with 73% of them suffering from infertility due to anovulation. This is a case report of 31-year old female complaining of scanty and painful menstruation. As she had a history of missed abortion at 6th week of gestation she was advised for ultrasound scan and her scan revealed bilateral polycystic ovarian syndrome. She also had anovulatory cycles on her follicular study. The treatment given aimed at correcting Vata kapha dushti, Agni mandya and Srotorodha. In this condition, Samana and Sodhana therapies were given. Samana chikitsa helped in Agni deepana and for normalising Vata kapha. Whereas Sodhana chikitsa helped in removing Srotorodha. Following that, Artava janaka dravyas and Rasayana chikitsa were given, which helped in correcting the Artava kshaya and proper Dhathu formation. The whole treatment may have contributed to accelerated maturation of graafian follicles. Thus the follicle ruptured and ovulation was detected in follicular study which highlights the potential action of ayurvedic treatment modalities in anovulatory cycles due to polycystic ovarian syndrome.